Analisis Nilai Moral dan Nilai Budaya dalam Cerita Rakyat pada Buku Siswa Tema 8 Kelas IV SD - Narendrani, Pramesthi Mega; Sukarno, Sukarno; Yulisetiani, Septi (Universitas Sebelas Maret, 2022)
Abstract. This research is to find out the moral and cultural values and the form of conveying the values in folklore in the 4th grade elementary school 8th theme student book. The research method used is a qualitative approach. The researcher used the object of the research on folklore in the in the 4th grade elementary school 8th theme student book. The data collection technique used is content analysis. The validity test used is triangulation theory, and time. Data analysis in this study uses the Miles & Huberman model, namely data reduction, data presentation, and drawing conclusions. The results of research on moral values consist of 4 forms, namely those that show human relationships with oneself, others, God, and nature. The most common forms of moral values are courage, mutual help, and compassion. The results of the study of cultural values consist of 5 forms, namely those that show the relationship between humans and God, society, other people, oneself, and nature. The most common forms of cultural values are love and help. The intersection of moral values and cultural values in this study is compassion, caring for others or helpers, helping or helping each other, helping each other or mutual cooperation, and caring for or preserving nature. The form of delivery of moral values and cultural values is presented directly and indirectly. The moral values and cultural values contained in this folklore can be used as an alternative to inculcating student character values through stories in student books.